Desenvolvimento de filmes biodegradáveis à base de zeína, caracterização das propriedades funcionais e estruturais e avaliação do uso como cobertura na conservação das características físico-químicas do queijo Minas padrão - Peña Serna, Carolina [UNESP] (2015)
Due to their chemical composition, foodstuffs may undergo quality and nutritional content deterioration as a consequence of factors such as microbiological contamination, contact with other foodstuffs or chemical compounds, the action of environmental agents as radiation (UV), air (oxygen), temperature variations, among others. Based on that, the food industry, aiming to protect and assure the quality and nutritional content of foodstuffs, is the greatest user of non-biodegradable packaging. In spite of that, the world's environmental concern due to the increase of the contamination and the accumulation of non-biodegradable packaging has promoted the development of biodegradable materials that allows for reducing the negative environmental impact as well as assures the food quality and nutritional content of foodstuffs. Thereby, food and packaging industries as well as several research institutions have focused their studies on the development of biodegradable packaging from sources such as agricultural residues and agroindustry by-products that are quickly degraded by soil microorganisms due to their natural origin. These packaging, mainly films and coatings, are based on biopolymers such as proteins (zein, collagen, gelatin, among others), carbohydrates (starch, chitosan, alginate, among others) and lipids (waxes and fatty acids). Zein, the main corn protein, has been used for industrial food and pharmaceutical applications; nonetheless, its use as an industrial packaging is limited due to its inferior physical, mechanical and structural properties compared to traditional plastic packaging. Based on that, several studies have demonstrated that combining two or more biopolymers as well as including plasticizer agents into the matrix of the biodegradable materials allows for improving the functional properties of the zeinbased films. Thus, in the first part of this study, different concentrations of ethanol (zein solvent) and glycerol...